Peran Media Sosial dalam Strategi Pemasaran Digital Hotel Baru: Studi Kasus di Semarang - Soegiarto, Kevin; Yuliamir, Henry (Mahesa Research Center, 2025)
This study aims to examine the role of social media in increasing brand awareness of newly established hotels in Semarang City that have been operating for a maximum of three years. The research is based on the growing importance of social media as an effective digital promotional tool, especially for new hotels that have yet to establish a strong reputation in the market. A qualitative approach was used with a case study method involving three new hotels: REZ Hotel Semarang, NusaTu Hotel, and KoenoKoeni Hotel. Data were collected through in-depth interviews with marketing managers and hotel guests, observation of social media activities, and digital documentation. The findings show that social media plays a significant role in shaping public perception of hotel brands through visual content, storytelling, and direct user interaction. All three hotels experienced an increase in followers, user engagement, and bookings from social media, particularly during the first six months of operation. Although challenges such as limited human resources and content consistency were noted, social media strategies proved effective and efficient in building brand awareness. These findings highlight the strategic importance of social media in the digital marketing of new hotels.